Peningkatan Keterampilan Mendeskripsikan Binatang dengan Bahasa Tulis Menggunakan Media Gambar Binatang Melalui Pendekatan Kontekstual pada Siswa Kelas 2 SD - Sahnim Sahnim (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
This study aims to determine the increase in writing skills in written grade II students of Elementary School. The implementation of this study uses classroom action research as one of the forms of qualitative research. This research was conducted in three cycles of research with the stages of planning, action, observation, and reflection. The results showed that learning through a contextual approach by utilizing animal image media can improve students' skills in writing in writing. This can be seen from the results of the study, namely the percentage before the implementation of the action is 27%, the first cycle is 45.4%, the second cycle is 59%, and in the third cycle reaches 86.3%. As per the percentage after the evaluation of the final results of the first cycle was 45.4%, the second cycle, 59%, and the final result of the third cycle was 86.3%, or included in the excellent category